Strategy Development of NoS-based Learning through Lecturer-Teacher Collaboration in Learning Innovation - ASTUTI, SRI DWI; SULISTIANTI, ERWIN; TRISILAWATI, TRISILAWATI (Bioedukasi: Jurnal Pendidikan Biologi, 2016)
This study was aimed to 1) improve qualit y of learning through the implementation of NoS based learning, 2) develop form of collaboration between teacher and lecturer in implementation of NoS based learning, 3) implementation NoS based learning model in Senior High School, 4) improve performance of lecturers-teachers through the implementation of based NoS learning, 5) improve learning outcomes on students. This study is a research based learning in Biology Education. The data of NoS covers teachers behavior, student behavior, learning climate and learning materials. The data was analyzed qualitatively. The results show that the implementation of NoS based learning in Biology Education had been appraised as very good by students (67.2%) and team teaching validated as very good (44.56%). Furthermore, students of SMA N 4 considered good (59.66%) and team teaching appraised as very good (81.9%). The students' outcomes had aslso been improved after implementation of NoS-based learning. It can be concluded that the NoS based learning is promised innovation in biology learning.